Microencapsulation Techniques in HIV Pediatric Formulations: Advances and Future Outlook - Nnamdi Ikemefuna Okafor (Advances in Pharmacological and Pharmaceutical Sciences)
The treatment of human immunodeficiency virus (HIV) in children has persistently been complex and tedious on a global scale. This is because adult and pediatric HIV treatments follow a similar therapeutic approach. Due to the dearth of clinically licensed pediatric antiretroviral drug (ARVD) therapy, children with HIV worldwide are prescribed unlicensed drugs each year. This has triggered likelihood of poor drug adherence, therapeutic failure, and even adverse reactions brought on by a variety of factors, including pill size and quantity, which is the main cause of swallowing difficulties, repeated administration of these various ARVDs, many of which have poor solubility and cause severe side effects in children, and unpalatability of the drug, which is one of the criteria for pediatric formulations. Thus, there is a necessity for investigation into several advanced microencapsulation techniques that could curb these challenges. Microencapsulation techniques have explored in drug delivery for encapsulation and manufacture of different nanoparticles that have shown significant potential in mitigating and surmounting different constraints, such as taste masking, enhanced drug solubility and bioavailability, and production of micronized fine powders for treatment of varying diseases. Nevertheless, the usage of these technologies in HIV pediatric formulations has garnered relatively little attention. Thus, this review has paid a keen interest in examining several microencapsulation strategies for potential utilization in the development of HIV pediatric formulations.